Діяльність Української греко-католицької церкви у підпіллі (1946–1989 рр.) - Стасюк, І. М. (Видавництво Львівської політехніки, 2014)
Статтю присвячено висвітленню однієї з найтрагічніших сторінок в історії Української греко-католицької церкви – її підпільному функціонуванню у 1946–1989 рр., тобто у часи її офіційного перебування поза законом. Основну увагу у дослідженні звернено на форми і методи діяльності у зазначений історичний період. This article is devoted to one of the most tragic pages in the history of the Ukrainian Greek Catholic Church - its underground operation in the 1946-1989 biennium, at the time of its official being outlawed. The main attention is paid to the study of form and methods of the specified historical period. The place and role of the church in the life of the Ukrainian people on the eve of its “ selfdestruct “ and highlighted the legal mechanism of destruction. Based on the above facts and statistics illustrated specific actions Greek Catholics in the fight for the legalization of the church: liturgy and administration needs in different places, unauthorized takeover of the churches for applications for registration of believers Greek Catholic communities and clergy disseminate information about the government’s decision a positive decision legitimate operation of the church. Also describes the measures the state in combating the spread of “ opium for the people” and the final destruction of the remnants uniatism. Considerable attention is given in the article personalities – their daily work on the development and strengthening of the underground. Highlighted as an activity of the church leadership, especially Y.Slipoho and ordinary priests. It is emphasized that their work was important for spiritual revival, as it does not contradict the Soviet legislation, including the Constitution of the USSR. The study analyzes the close relationship of the underground Ukrainian Catholic Church of the center – the Vatican, are examples of their close cooperation on religious matters, especially in trying to official legalization of the Ukrainian Greek Catholic Church. In the context of the religious policy of the government highlights the problem of the scale of the underground church in different decades. There is both a negative and a positive effect on the size and number of the faithful of the UGCC policymaking Union- Republican government.
Keywords: Греко-католицька церква; підпілля; Й. Сліпий; Greek Catholic Church; underground; Y. Slipy